PENGARUH KEPEMIMPINAN DAN INSENTIF TERHADAP KINERJA KARYAWAN PT MASYITHAH YARSI SUMBAR BAGIAN CLEANING SERVIS PADA RUMAH SAKIT IBNU SINA BUKITTINGGI - Rina Supryanita; Nurfitriyenny Nurfitriyenny; Dian Rahmawaty; Fitria Fitria; Luthfi Suhud (Komunitas Manajemen Kompetitif, 2025)
Abstract Employees at PT Masyithah Yarsi Sumbar Cleaning Service Department at Ibnu Sina Hospital Bukittinggi experienced significant variation in achieving monthly performance targets. Some months their performance showed quite good improvement, but in certain months there was a significant decline. There was a low desire from some employees to achieve the targets that had been set, which may be caused by unclear direction and support from the leadership, as well as inadequate incentives. This study aims to examine the effect of leadership and incentives on the performance of employees of PT Masyithah Yarsi Sumbar Cleaning Service Department at Ibnu Sina Hospital Bukittinggi. This study used quantitative methods. The type of data in this study is primary data obtained by distributing questionnaires to employees of PT Masyithah Yarsi Sumbar Cleaning Service Department at Ibnu Sina Hospital Bukittinggi. The sampling technique used was purposive sampling; the number of employees sampled in this study was 33 people who used the accounting information system. The analysis technique uses a test tool with the help of SmartPLS software version 3. Based on the results of the hypothesis testing that have been described in the research results, it shows that leadership has a positive but not significant effect on employee performance, and incentives have a positive and significant effect on employee performance.